2012
DOI: 10.1063/1.4751872
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear electron-magnetohydrodynamic simulations of three dimensional current shear instability

Abstract: This paper deals with detailed nonlinear electron-magnetohydrodynamic simulations of a three dimensional current shear driven instability in slab geometry. The simulations show the development of the instability in the current shear layer in the linear regime leading to the generation of electromagnetic turbulence in the nonlinear regime. The electromagnetic turbulence is first generated in the unstable shear layer and then spreads into the stable regions. The turbulence spectrum shows a new kind of anisotropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…approximation have been reported earlier [15][16][17][18][19][20][21] . In EMHD the electron flow carries the current.…”
Section: Investigations Of Linear and Nonlinear Electron Shear Flow Isupporting
confidence: 71%
“…approximation have been reported earlier [15][16][17][18][19][20][21] . In EMHD the electron flow carries the current.…”
Section: Investigations Of Linear and Nonlinear Electron Shear Flow Isupporting
confidence: 71%
“…Linear and nonlinear studies of electron shear flow instabilities in EMHD approximation have earlier been performed. [29][30][31][32][33][34][35] These instabilities have also been referred as current driven sausage and kink instabilities because, in EMHD, electron flow is equivalent to current. 30,32,33 Comparison of growth rates of 2-D instabilities in the plane containing directions of flow and shear (termed pure sausage mode) was made with the 2-D instabilities in the plane perpendicular to the sausage plane (termed pure kink mode).…”
Section: Introductionmentioning
confidence: 98%
“…However, recent experiments have shown that for sharp overdense plasmas (with an interface with a scale length \ $ light vacuum wavelength) which naturally result when the pulses are so short that CPA (Mourou 1997) leads to relativistic intensities, standard resonance absorption was replaced by Brunel mechanism which converted light energy into relativistic electron beams with energy of the order of few MeV. The subsequent propagation of relativistic beams into overdense plasmas has led to some very novel physics and resulted in a very fruitful collaboration between our group at IPR (led by Amita Das) and experimental groups at TIFR (GRK) and Osaka (KaT) (Sandhu et al 2002;Kahaly et al 2008;Mondal et al 2012;Das and Kaw 2001;Jain et al 2003;Sandhu et al 2005;Saxena et al 2006Saxena et al , 2007Jain et al 2007Jain et al , 2012Kahaly et al 2009;Yadav et al 2008Yadav et al , 2009Yadav and Das 2010;Gaur et al 2009;Sundar et al 2011). I shall also briefly summarize this work, in which I have actively participated, during the past decade or more.…”
Section: Early History Of Conceptual Advances In Laser-plasma Interacmentioning
confidence: 99%